HUBUNGAN MINAT BELAJAR DENGAN KENAKALAN REMAJA KELAS XII DI SMK TI PABAKU STABAT - Sinarsi Meliala; Siska Dwi Ningsih; Sri Ramadhani; Syahri Putra Banurea (Psikologi Universitas Sari Mutiara Indonesia, 2021)
Panca Baku Abdi (PABAKU) Stabat Private Vocational School, which is located at Jl. Pringgodani No. 813, Karangrejo, Stabat District, Langkat Regency, North Sumatra. With the status of ownership of the foundation, and accredited B. is shaded by the principal, Mrs. Sri Ramadhani and Mrs. Susi Linawati as the operator, with a learning schedule that is held in the morning.PABAKU Stabat Private Vocational School consists of 8 classes, and is divided into 3 majors, namely; Light Vehicle Engineering (TKR), Computer Network Engineering (TKJ), and Office Administration (ADP).This type of research is a quantitative research with a number of subjects of 80 students, selected by purposive sampling, from the subject data collected using a scale of interest in learning and juvenile delinquency. The results showed that the correlation value was -0.259 (P> 0.05), the linear value was 0.122 (P> 0.05). This means the results of the study are linear. The data were analyzed using the nonparametic correlation analysis technique and the results obtained were r = -0.259 and a significance value of 0> (0.05), this states that the relationship between learning interest and juvenile delinquency is accepted which means that Ha is accepted and H0 is rejected. Thus, there is a relationship between interest in learning and juvenile delinquency.